Effects of different holding temperatures before freezing on the quality of bull semen - Thien, Ivy Shuk Yee (2017)
A study was conducted to evaluate the effect of different holding temperature before freezing on the motility, morphology and viability of chilled and frozen bull spermatozoa. Semen collection was performed on four mature bulls by electro ejaculator. After initial evaluation and first dilution using Tris-egg yolk semen extender, four groups of diluted semen samples were kept in four different holding temperatures (4°C, 15°C, 25°C and 37°C) for 10 minutes. All semen samples were subsequently chilled in refrigerator at 4°C for at least 3 hours. Post chilling evaluation was done after second dilution with the same extender added with glycerol. The semen samples were packed into 0.25ml straws before freezing into liquid nitrogen. Thawing of frozen semen samples were done on day 1 post cryopreservation in water maintained at 37°C for 30 seconds. Semen evaluation was conducted post thawing. The results showed that there were no significant difference among the four different holding temperatures for the post chilling and frozen thawed sperm motility, morphology and viability. Based on the findings of this study, it can be concluded that 10 minutes holding time at different holding temperatures before freezing did not affect the quality of chilled and frozen bull spermatozoa.